Carotenoid intake and adipose tissue carotenoid levels in relation to prostate cancer aggressiveness among African‐American and European‐American men in the North Carolina–Louisiana prostate cancer project (PCaP). Issue 12 (8th June 2016) - Antwi, Samuel O.; Steck, Susan E.; Su, L. Joseph; Hebert, James R.; Zhang, Hongmei; Craft, Neal E.; Fontham, Elizabeth T.H.; Smith, Gary J.; Bensen, Jeannette T.; Mohler, James L.; Arab, Lenore
Abstract : BACKGROUND: Associations between carotenoid intake and prostate cancer (CaP) incidence have varied across studies. This may result from combining indolent with aggressive disease in most studies. This study examined whether carotenoid intake and adipose tissue carotenoid levels were inversely associated with CaP aggressiveness. METHODS: Data on African‐American (AA, n = 1, 023) and European‐American (EA, n = 1, 079) men with incident CaP from North Carolina and Louisiana were analyzed. Dietary carotenoid intake was assessed using a detailed‐food frequency questionnaire (FFQ), and abdominal adipose tissue samples were analyzed for carotenoid concentrations using high‐performance liquid chromatography. Multivariable logistic regression was used in race‐stratified analyses to calculate odds ratios (ORs) and 95% confidence intervals (95%CI) comparing high aggressive CaP with low/intermediate aggressive CaP. RESULTS: Carotenoid intake differed significantly between AAs and EAs, which included higher intake of lycopene among EAs and higher β−cryptoxanthin intake among AAs. Comparing the highest and lowest tertiles, dietary lycopene was associated inversely with high aggressive CaP among EAs (OR = 0.55, 95%CI: 0.34–0.89, Ptrend  = 0.02), while an inverse association was observed between dietary β−cryptoxanthin intake and high aggressive CaP among AAs (OR = 0.56, 95%CI: 0.36–0.87, Ptrend  = 0.01). Adipose tissue α−carotene and lycopene ( cis  +  trans ) concentrations were higher among EAs than AAs, and marginally significant inverse linear trends were observed for adipose α−carotene (Ptrend  = 0.07) and lycopene (Ptrend  = 0.11), and CaP aggressiveness among EAs only. CONCLUSIONS: These results suggest that diets high in lycopene and β−cryptoxanthin may protect against aggressive CaP among EAs and AAs, respectively. Differences in dietary behaviors may explain the observed racial differences in associations. Prostate 76:1053–1066, 2016 . © 2016 Wiley Periodicals, Inc.